2015
DOI: 10.1590/0100-2945-002/14
|View full text |Cite
|
Sign up to set email alerts
|

VARIABILIDAD GENÉTICA DE PARENTALES Y POBLACIONES F1 INTER E INTRAESPECÍFICAS DE Physalis peruviana L. Y P. floridana Rydb.

Abstract: RESUMEN -La uchuva, Physalis peruviana, es un frutal andino de importancia para la exportación; el principal limitante de su producción en Colombia es el marchitamiento vascular ocasionado por Fusarium oxysporum. En el presente trabajo se propuso generar poblaciones F 1 entre parentales contrastantes por su respuesta a éste patógeno y evaluarlas molecularmente como apoyo al conocimiento y uso de los recursos genéticos de la especie. Para ello, cuatro genotipos de P. peruviana y uno de la especie relacionada P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
8
0
2
Order By: Relevance
“…Las tres poblaciones mostraron baja diversidad genética, incluso San Pablo presentó nula. Los valores bajos de diversidad genética se generan por la presencia de una población estructurada, que puede ser generada en poblaciones cultivadas por dos razones principales: (1) el tipo de reproducción vegetal, principalmente en autógamas, lo cual no es el caso pues aguaymanto es principalmente alógama (Cely et al 2015) y (2) la presencia de un programa de mejora genetica; esto último fue mencionado por los representantes de las empresas que cultivan los denominados ecotipos Agroandino y Celendino, quienes aplican el método de selección de masal. Por lo tanto, esta sería la razón de la baja diversidad genética encontrada.…”
Section: Discussionunclassified
“…Las tres poblaciones mostraron baja diversidad genética, incluso San Pablo presentó nula. Los valores bajos de diversidad genética se generan por la presencia de una población estructurada, que puede ser generada en poblaciones cultivadas por dos razones principales: (1) el tipo de reproducción vegetal, principalmente en autógamas, lo cual no es el caso pues aguaymanto es principalmente alógama (Cely et al 2015) y (2) la presencia de un programa de mejora genetica; esto último fue mencionado por los representantes de las empresas que cultivan los denominados ecotipos Agroandino y Celendino, quienes aplican el método de selección de masal. Por lo tanto, esta sería la razón de la baja diversidad genética encontrada.…”
Section: Discussionunclassified
“…Consequently, we could carry out intraspecific crosses among genotypes with the same chromosomal numbers, expecting to obtain viable and stable progeny. A precedent example of the success of crossing between genotypes with the same ploidy is the work of Berdugo et al, (2015). In their study the authors made intraspecific crosses among accessions of P. peruviana with the same chromosome number, finding 100% viability in the progeny.…”
Section: Crossability Strategiesmentioning
confidence: 99%
“…Liberato et al, (2014) determined chromosome numbers of 2n = 4x = 48 and 2n = 2x = 24 that correlated with the nuclear DNA content estimated by flow cytometry. In addition, Berdugo et al, (2015) carried out crosses between some genotypes analyzed by Liberato et al, (2014) and found distortion in the segregation, possibly related to differences in the chromosome size or chromosome number of these materials. The cytogenetic variability, found in the collection of the germplasm bank maintained at Agrosavia and in the working collections, highlights the importance of knowing the cytogenetic identity of each genotype before its inclusion in hybridization-based breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…They detected a low differentiation and high heterozygosity levels among the majority of the accessions [20,21]. Other studies used more informative markers, such as simple sequences repeats (SSRs), conserved ortholog sequences II (COSII), immunity related genes (IRGs) and single nucleotide polymorphisms (SNPs) to analyze the diversity levels and population structure in natural and breeding P. peruviana populations [22][23][24][25][26]. However, these low-throughput platforms provide a limited ability to estimate the extent of cape gooseberry genetic variability, since they focus on limited genomic regions.…”
Section: Introductionmentioning
confidence: 99%